2- Ethics and the Non-physical Self in Ndorobo World View - Ashdown, Shelly (African Sociological Review, 2009)
Ethics in Ndorobo world view are concerned primarily with Self and its effect on the welfare and moral state of community Other. Significant psychical elements of Self such as personality, character, honesty, desire, and decision can affect the state of community strength through personal behaviour deemed ethical or unethical. Ndorobo ethics is concerned exclusively with governing social conduct for interpersonal relations. This article proposes that elements of the non-physical Self are sources for moral behaviour, and social customary law is the basis for moral duty among the Ndorobo. Germane to the discussion are the roles associated with the non-physical Self that reflect four basic ethical principles in Ndorobo world view: 1) Ethical principle of social unity; 2) Ethical principle of relational exchange; 3) Ethical principle of respect; and 4) Ethical principle of role standards. Conformity to role expectations by Self is highly valued as an ethical axiom that is viewed as natural and necessary in the life of a Ndorobo.